2010
DOI: 10.1111/j.1439-0418.2010.01584.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of sterile Mediterranean fruit fly (Diptera: Tephritidae) males to ginger root oil reduces female remating

Abstract: Females of Ceratitis capitata are facultative polyandrous, with remating more common in laboratory strains rather than wild ones. In the application of the Sterile Insect Technique (SIT) against this pest, large overflooding ratios of sterile : wild males can increase the remating frequency. Females that mate for the first time with a sterile male tend to remate more frequently. The exposure of sterile males to ginger root oil (GRO) is used in C. capitata SIT programmes to increase the sterile male mating succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
42
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 46 publications
3
42
0
1
Order By: Relevance
“…Thus, we observed that the lowest tested concentration of GRO could be optimally and successfully used for C. capitata aromatherapy in operational SIT programmes. Also, Morelli et al. (2013) working with the same dose (0.1 ml of GRO/m 3 ) found that male exposure to GRO aroma resulted in a reduction of female receptivity after mating, comparable to matings with wild males.…”
Section: Discussionmentioning
confidence: 81%
“…Thus, we observed that the lowest tested concentration of GRO could be optimally and successfully used for C. capitata aromatherapy in operational SIT programmes. Also, Morelli et al. (2013) working with the same dose (0.1 ml of GRO/m 3 ) found that male exposure to GRO aroma resulted in a reduction of female receptivity after mating, comparable to matings with wild males.…”
Section: Discussionmentioning
confidence: 81%
“…(), Morelli et al. () exposed mature male medflies to ginger root oil and found that the remating propensity of their mates was halved in comparison with mates of untreated males. While there has been substantial exploration of pre‐release treatments targeting mature adult male fruit flies in terms of mating propensity or competitiveness, much remains to be learned about the effects of development/mating enhancers on post‐copulatory processes that determine how successful a copulation will be in affecting female remating decisions and reproductive success (Pérez‐Staples et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The mating performance of sterile males includes traits such as the ability to compete in leks to transfer sperm to females effectively and to reduce the risk of females remating . Previous studies had stated the capacity of GRO‐treated sterile C. capitata males successfully to compete with wt males by counting mating pairs in field cages and, under laboratory conditions, by their capacity to avoid remating of females . In this study, the observed reduction in the number of puparia per fruit and the corresponding reduction in the following C. capitata generation suggest that GRO‐treated sterile VIENNA‐8 males were able efficiently to compete in leks, in transferring sperm and in remating under natural conditions (data not shown).…”
Section: Discussionmentioning
confidence: 60%